MODEL SISTEM INFORMASI PENJAMINAN MUTU BERBASIS INTERGRASI AKREDITASI BAN-PT DAN ISO 9001:2008 DENGAN PENDEKATAN METODE EKD-CM - Mercurius Broto Legowo; Budi Indiarto; Deden Prayitno (IST AKPRIND Yogyakarta, 2018)
The purpose of this research is to develop a model of quality assurance information system based on integration of BAN-PT accreditation and ISO 9001: 2008 for ISO certified university, using the approach of